Implementation of Socially Inclusive Principles by MSME Actors in the Culinary Area of Beran Field Madiun - Afrida Rosa Marsela; Nurma Fitrianna; Rofiqus Sa’adah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research addresses a significant gap in understanding how social inclusive principles are applied within the green economy framework among culinary Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in the culinary area of Beran Field, Madiun Regency, East Java. Despite growing awareness of green economy concepts, there is limited empirical evidence on how MSMEs integrate social inclusion alongside environmental sustainability in their business practices. This study employs a qualitative field research approach, utilizing in-depth interviews, participant observations, and document analysis to explore the experiences and perspectives of MSME owners and stakeholders in the Beran Field culinary area. Data were collected from 5 MSME actors selected through purposive sampling to ensure diverse representation. The findings reveal that some business owners have adopted inclusive practices such as affordable pricing, flexible payment options, and open access for all community members regardless of social background. However, several MSMEs demonstrate a limited understanding of social inclusion, prioritizing commercial objectives over inclusive values. This inconsistency highlights a gap in awareness and practical application of social inclusiveness within the green economy framework. The study concludes that while initial efforts to implement socially inclusive principles exist, more structured support, including capacity building and policy incentives, is necessary to enhance social inclusion among MSMEs. Strengthening social inclusion can foster a more equitable, sustainable, and environmentally friendly business environment, ultimately improving business competitiveness and contributing to climate resilience. The main takeaway is that social inclusiveness is critical to achieving a green economy that benefits both society and the environment.